The Polar Express - Zemeckis, Robert, 1952-; Hanks, Tom.; Zemeckis, Leslie Harter; Deezen, Eddie, 1958-; Gaye, Nona.; Scolari, Peter, 1954-; Ballard, Glen.; Van Allsburg, Chris; Warner Home Video (Firm) (Burbank, Calif. : Warner Home Video, 2005)
When a doubting young boy takes an extraordinary train ride to the North Pole, he embarks on a journey of self-discovery that shows him that the wonder of life never fades for those who believe.
Title from container.
Full screen.
Originally released as a motion picture in 2004.
Based on the book by Chris Van Allsburg.
Directors of photography, Don Burgess, Robert Presley ; editors, Jeremiah O'Driscoll, R. Orlando Duenas ; music, Alan Silvestri, Glen Ballard ; costume designer, Joanna Johnston ; production designers, Rick Carter, Doug Chiang.
Tom Hanks, Leslie Harter Zemeckis, Eddie Deezen, Nona Gaye, Peter Scolari, Brendan King, Andy Pellick, Josh Eli, Mark Mendonca, Rolandas Hendricks.
Keywords: Films for the hearing impaired; North Pole -- Juvenile drama; Christmas films; Feature films; Children's films